Peran Sosial Umat Dalam Membangun Solidaritas Menurut Tafsir Surah At-Taubah Ayat 71 - Hesti Agusti Saputri; Siti Nur Kholifah; Farzila Wati; Rajif Adi Sahroni (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This study discusses the social role of the ummah in building solidarity based on the interpretation of Surah At-Tawbah verse 71. The study method used is to use literature review. This study outlines the concept of solidarity in Islam and how Muslims can play an important role in strengthening solidarity in society. By analyzing the interpretation of verse 71 of Surah At-Tawbah, this article highlights the importance of cooperation, help, and social care in creating strong solidarity among Muslims.